Read, write, develop: The social and economic impact of literacy in South Africa - Khumalo, Ziyanda (Graduate School of Business (GSB), 2020)
The topic of literacy has received a decent amount of attention over the years both academically and from various institutions and forums across the globe. The increased focus on addressing illiteracy drove the global illiteracy rate down from 40% in 1970 to 25% in 1990. Initiatives to promote universal literacy began as far back as the early 1950s yet the latest available data on literacy from UNESCO Institute for Statistics (UIS) indicates that 750 million adults in the world are still illiterate. With a world population of approximately 7.6 billion, that translates to one in every 10 people. Regionally, sub-Saharan Africa (SSA) and Southern Asia host the world's lowest literacy rates with a combined 20 countries holding literacy rates of below 50% while Central, Eastern and South-Eastern Asia, Europe and Northern America have literacy rates close to or at 100%. South Africa was rated number 50 out of 50 countries that participated in the Progress in International Reading Literacy Study (PIRLS) of grade four learners in 2016. Against this background, this study sought to provide insight on the social and economic impact of literacy in South Africa with a focus on how literacy influences unemployment, the HIV prevalence rate, crime and income inequality. The study employed fixed and random effects techniques to estimate a panel data of nine (9) provinces between 2008 and 2017. A provincial average of 90.79% for the literacy rate was derived from the data ranging from a minimum of 81.13% to a maximum of 98.10%. Gauteng had the highest literacy rate while the Northern Cape had the lowest. Gauteng also came out as the province with the highest average GDP per capita (GDPPC) while the Northern Cape had the lowest average crime and unemployment rates. The provincial averages for the dependent variables were 25.70% for the unemployment rate, 17.50% for the HIV rate, 1.13% for the crime rate and ZAR63,029 for GDPPC. The results showed that literacy was positively related to unemployment, HIV and GDPPC which indicate that increases in the literacy rate resulted in higher unemployment and HIV prevalent rates and higher income per capita across the nine provinces in South Africa. When the crime rate was analysed as the dependent variable, the results showed a positive correlation with literacy in the absence of unobserved variables and a negative correlation with literacy when unobserved variables were included. On the back of this study's results, which indicated a positive relationship between literacy and unemployment as well as GDPPC, policymakers need to consider an expanded view and focus of literacy by including financial, health and technology literacy and investing in those in addition to functional literacy. Furthermore, government needs to initiate a nationwide literacy campaign which targets communities with high illiteracy rates 2 across the country. This campaign would focus on reducing illiteracy with the primary objective of educating the community not only about HIV but the importance of HIV testing as well. Lastly, literacy campaigns need to integrate education on how the community can work with the police to combat crime as greater community participation could lower the crime rate